PERAN GURU DALAM MENUMBUHKAN KEMANDIRIAN ANAK BERDASARKAN POLA ASUH ORANG TUA DI RA JABAL NUR TLOGOWARU KEDUNGKANDANG KOTA MALANG - Ghora Vira Laras Baja; Mohammad Afifulloh; Ika Anggraheni (Jurnal Dewantara, 2020)
Importance point about childhood independence is a children can running his own self’s life without depends on other people and around. Researcher do first observation to The children’s in RA Jabal Nur Tlogowaru Kedungkandang Kota Malang.On there, self children’s independence was not running well. Some children still have their own depend to the teacher, frind, and their parent’s. The problem that often be happen is when the children entry to the scholl environment beginning. Authoritarian parenting is a very assertive parenting’s shape. There are view of the rule inside. The children’s always accustomed to gift and punishment.For example is  Arya and Uwais who always the gift for  every good think if they want to do. Authoritarian is a parenting shape can make a child will be a independence, assertive with his ownself, and will be kind personal  to their friend. in otherwise, permissive parenting not giving some border and it can make a spoiled person. It looks like in Azizah, Rani, and Nabila. They can said not a independence children, because they are still depend on their parent’s and around people there. Authoritarian parenting also basiccly from respect and understanding from parents to their kid. The parent who use this way give some rule that suitable for children’s age. It looks like Fattah. He can do some responsibility to his ownself and he can be adaptation with pepole’s around. The results showing  that parenting from the parent’s in RA Jabal Nur Tlogowaru Kedungkandang Malang City is a Authoritarian parenting and permissive parenting. Role of the teacher to parenting shape is always give some motivation to childrens. Teacher should be can do motivate and corrector for parents who doing this shape parenting. In Other side, teacher Should be a motivator person and inpirator for teh childrens.